(untitled) (Revista Innova Educación, 2022)
In Peru, during the COVID-19 pandemic, special regulations were developed that allowed the continuity of higher education through virtual teaching. In this context, the guidelines for remote work were established, the application of which included public and private workers. In addition, university professors have been an important factor in ensuring the continuity of academic activities and influencing the performance of universities. The objective of the article was to analyze the documentary sources on the relationship between remote work and job satisfaction of Peruvian university professors before and during the COVID-19 pandemic. The methodology used was documentary research. The results show that remote work was not a new type of employment and that in Peru it was established and implemented without the necessary legal framework and technological support. In addition, the different teaching modalities can influence the job satisfaction of university professors. Finally, remote work and the pandemic have influenced the job satisfaction of workers, including university professors. It is concluded that studies on remote work and job satisfaction of university teachers show that there is a relationship between both variables; that is, remote work can influence the level of job satisfaction of Peruvian university professors.